Oxygen carrier derived from metal doped / cellulose intercalated hydrotalcite-like compound as well as preparation and application of oxygen carrier

The metal-doped/cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier addresses high-temperature inefficiencies by enhancing oxygen release and catalytic activity, achieving efficient hydrogen production with reduced energy consumption and metal recovery.

CN119242361APending Publication Date: 2025-01-03SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411431366.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Current oxygen carriers used in hydrogen production suffer from high thermodynamic limitations, leading to high reaction temperatures that cause sintering and carbon deposition, resulting in energy waste and inefficient oxygen release and catalytic activity.

Method used

A method for preparing a metal-doped/cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier through steps of cellulose intercalation and calcination, which enhances oxygen release capacity and catalytic activity at medium and low temperatures.

Benefits of technology

The oxygen carrier exhibits improved oxygen release capacity, catalytic activity, and anti-sintering properties, maintaining high H2 and CO selectivity and conversion rates, while also enabling the recovery and utilization of rare earth metals or toxic metals from wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242361A_ABST
    Figure CN119242361A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen carrier derived from a metal doped / cellulose intercalated Ni-Fe-Al hydrotalcite-like compound as well as preparation and application of the oxygen carrier. The hydrotalcite-like compound capable of being assembled on the molecular level is prepared through a coprecipitation method, cellulose is introduced into the interlayer of the hydrotalcite-like compound in an interlayer insertion mode, the purpose of separating rare earth or toxic metal in waste water is achieved by adsorbing metal in the waste water, and then the rare earth or toxic metal in the waste water is separated through thermal conversion. The high-metal-dispersity cellulose intercalation hydrotalcite-like oxygen carrier doped and modified by the rare earth or the toxic metal is obtained, and the oxygen carrier prepared by the method has proper oxygen release capacity and catalytic activity due to the doping and modification effect of the rare earth or the toxic metal; and the oxygen carrier also has good fuel conversion rate, synthesis gas selectivity and carbon deposition resistance at medium and low temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oxygen carriers, and in particular relates to an oxygen carrier derived from metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite and a preparation method and application thereof. Background Art

[0002] As an ideal carrier of carbon-neutral energy pathways, hydrogen energy has become one of the most promising candidates for meeting future energy needs and achieving a carbon-free world. However, large-scale hydrogen production is often susceptible to contamination by carbonaceous and non-carbonaceous impurities, and the separation and purification of the product results in a large amount of energy consumption.

[0003] Chemical chaining steam reforming provides an effective solution to this problem: using oxygen carriers (OC) as carriers for recycling in fuel reactors and steam reactors, carbon-based fuels and water vapor are converted into synthesis gas and hydrogen, respectively, effectively reducing separation costs. Oxygen carriers with good lattice oxygen transmission capacity, catalytic ability, and long-term cycle stability have become the key to the development of this technology.

[0004] Hydrotalcite-like compounds are layered hydroxides that not only have uniform dispersion at the metal cation molecular level, but can also be used as a main matrix for the synthesis of organic-inorganic nanocomposites through ion exchange. The oxygen carrier formed by calcining hydrotalcite-like compounds has the characteristics of high dispersion at the metal molecular level. However, due to thermodynamic limitations, the current optimal reaction temperature of the oxygen carrier is relatively high (800-950°C), which not only leads to the risk of high-temperature sintering and carbon deposition of the oxygen carrier, but also leads to huge energy waste. Therefore, how to improve the oxygen release capacity and catalytic ability of the oxygen carrier in the medium and low temperature stages is of great significance. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing an oxygen carrier derived from metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite.

[0006] Another object of the present invention is to provide an oxygen carrier derived from a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-like substance obtained by the above-mentioned preparation method.

[0007] Another object of the present invention is to provide an application of the oxygen carrier derived from the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier comprises the following steps:

[0010] (1) adding cellulose to a mixed solution of urea and alkali salt to prepare a cellulose mixed alkali solution;

[0011] (2) adding a mixed aqueous solution of nickel salt, aluminum salt and iron salt to a mixed alkaline solution of cellulose for coprecipitation, aging, filtering, washing and drying to obtain a cellulose intercalated hydrotalcite precursor;

[0012] (3) adding the cellulose intercalated hydrotalcite precursor into a metal solution or metal wastewater for immersion adsorption, filtering, washing, and drying to obtain a cellulose intercalated Ni-Fe-Al hydrotalcite composite with interlayer adsorption of metal;

[0013] (4) The cellulose intercalated Ni-Fe-Al type hydrotalcite composite with interlayer adsorbed metal is calcined at 400-900° C. for 4-8 hours to obtain a metal-doped / cellulose intercalated Ni-Fe-Al type hydrotalcite-derived oxygen carrier.

[0014] Preferably, the average particle size of the cellulose in step (1) is 50 to 200 μm.

[0015] Preferably, in the mixed solution of urea and alkali salt in step (1), the molar ratio of urea to alkali salt is 1-2:1; more preferably 1.14:1; and the alkali salt is at least one of sodium hydroxide and potassium hydroxide.

[0016] Preferably, in the mixed solution of urea and alkali salt in step (1), the total molar concentration of urea and alkali salt is 3.75-6 mol / L; more preferably 3.75 mol / L.

[0017] Preferably, the temperature of the mixed solution of urea and alkali salt in step (1) is 10-30°C; more preferably 12°C.

[0018] Preferably, the total molar ratio of the mass of the cellulose to the mass of the urea and the alkali salt in step (1) is 8.37-16.74 g:1 mol; more preferably 8.37 g:1 mol.

[0019] Preferably, the preparation in step (1) is carried out at a stirring speed of 500 to 800 r / min; and the stirring time is 60 to 120 min.

[0020] Preferably, the molar ratio of the mass of the cellulose in step (1) to the total metal of the nickel salt, the aluminum salt and the iron salt is 62.8-125.6 g:1 mol; more preferably 62.8:1 mol.

[0021] Preferably, the nickel salt in step (2) is nickel nitrate; the aluminum salt is aluminum nitrate; and the iron salt is iron nitrate.

[0022] Preferably, the molar ratio of the nickel salt, iron salt and aluminum salt in step (2) is 2-3:1:1; more preferably 2:1:1.

[0023] Preferably, in the mixed aqueous solution of nickel salt, aluminum salt and iron salt in step (2), the total concentration of cations is 0.1 to 1 mol / L, more preferably 1 mol / L.

[0024] Preferably, the coprecipitation in step (2) is carried out at a stirring speed of 500 to 800 r / min.

[0025] Preferably, the coprecipitation time in step (2) is 10 to 25 minutes.

[0026] Preferably, the aging time in step (2) is 12 to 24 hours.

[0027] Preferably, the washing in step (2) refers to washing with water until it becomes neutral.

[0028] Preferably, the drying temperature in step (2) is 70 to 120° C. and the drying time is 15 to 24 hours.

[0029] Preferably, the immersion adsorption in step (3) is carried out at a stirring speed of 200 to 500 r / min.

[0030] Preferably, the soaking and adsorption time in step (3) is 60 to 240 minutes.

[0031] Preferably, the temperature of the soaking adsorption in step (3) is 10 to 35°C.

[0032] Preferably, in the metal solution and metal wastewater of step (3), the metal is at least one of La, Y, Ce, Zr and Cr; more preferably at least one of La, Y and Cr; the metal exists in the solution and wastewater in the form of soluble salts; the soluble salts are further preferably nitrates.

[0033] Preferably, the concentration of the metal in the metal solution and metal wastewater in step (3) is 0.05-0.25 mol / L; more preferably 0.15 mol / L.

[0034] Preferably, the mass ratio of the cellulose intercalated Ni-Fe-Al hydrotalcite composite in step (3) to the total molar ratio of metal cations in the metal solution or metal wastewater is 1 g: 1 to 5 mmol; more preferably 1 g: 3 mmol.

[0035] Preferably, the washing in step (3) refers to washing with water until it becomes neutral.

[0036] Preferably, the drying temperature in step (3) is 70 to 120° C. and the drying time is 2 to 24 hours.

[0037] Preferably, the calcination temperature in step (4) is 500-900°C, and the time is 2-6 hours; more preferably, the calcination is calcined at 500°C for 2 hours and then at 900°C for 4 hours.

[0038] Preferably, the calcination in step (4) is carried out under an air atmosphere.

[0039] Preferably, the heating rate of the calcination in step (4) is 2-15°C / min; more preferably 10°C / min.

[0040] Preferably, after the cellulose intercalated Ni-Fe-Al hydrotalcite composite with interlayer metal adsorption in step (4) is calcined, it is further ground and sieved; more preferably, the sieving refers to sieving through an 80-mesh sieve.

[0041] The preparation method is a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0042] The above-mentioned metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier is used in chemical chaining water vapor to produce synthesis gas and pure hydrogen.

[0043] Preferably, the application is specifically as follows: adding the above-mentioned metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier into a fuel reactor, first introducing an inert gas to purge the air in the fuel reactor, then heating the fuel reactor to a reaction temperature, and after the temperature of the fuel reactor is stable, introducing gaseous fuel, liquid fuel or solid fuel to produce synthesis gas (a mixture of H2 and CO), after the reaction is completed, introducing an inert gas to purge the synthesis gas in the reactor, and after the steam reactor is stable, introducing water vapor and inert gas for steam reforming to produce hydrogen.

[0044] More preferably, the gas fuel is an alkane fuel diluted with an inert gas to a volume percentage of 5 to 25%; the liquid fuel is an alcohol or bio-oil fuel; and the solid fuel is biomass or organic waste solid fuel.

[0045] More preferably, the gas fuel is methane diluted with an inert gas to a volume percentage of 5 to 25%.

[0046] More preferably, the flow rate of the inert gas is 90-100 ml / min, and the introduction time (inert gas purge) is 5-10 min.

[0047] More preferably, the flow rate of the gas fuel is 50-150 ml / min, and the introduction time is 20-180 min; more preferably 27 min.

[0048] More preferably, the lattice oxygen molar ratio of the gas fuel, liquid fuel or solid fuel to the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier is 1.2 to 0.8:1.

[0049] More preferably, the molar ratio of the water vapor to the lattice oxygen in the oxygen carrier derived from the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite is 0.82-8.2:1.

[0050] More preferably, the flow rate of the inert gas in the steam reforming stage is 50-100 ml / min.

[0051] More preferably, the reaction temperature is 500-900°C; more preferably 750-900°C.

[0052] More preferably, the steam injection rate during the steam reforming process is 0.1 to 10 ml / min; the time is 20 to 180 min; more preferably 27 min.

[0053] The present invention separately introduces gaseous fuels such as alkanes, liquid fuels such as alcohols and bio-oils, and solid fuels such as biomass and organic waste solids into a fuel reactor, introduces water vapor into a steam reactor, and catalytically oxidizes and reduces oxygen carriers derived from metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcites with good lattice oxygen transmission and activation capabilities to prepare synthesis gas and hydrogen.

[0054] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0055] (1) The present invention prepares a hydrotalcite-like substance that can be assembled at the molecular level by a coprecipitation method, introduces cellulose into the interlayer of the hydrotalcite-like substance by interlayer insertion, and achieves the purpose of separating rare earth metals or toxic metals in wastewater by adsorbing rare earth metals or toxic metals. After thermal conversion, a high metal dispersibility oxygen carrier doped and modified with rare earth metals or toxic metals is obtained. The oxygen carrier prepared by this method has suitable oxygen release capacity and catalytic activity due to the doping and modification of rare earth metals or toxic metals, so that the oxygen carrier also has good fuel conversion rate, synthesis gas selectivity and anti-carbon deposition ability at medium and low temperatures.

[0056] (2) In the process of preparing a composite having rare earth metal interlayer adsorption capacity by cellulose intercalation Ni-Fe-Al type hydrotalcite of the present invention, wastewater containing rare earth metals or toxic metals is used as one of the raw materials, and the rare earth metals or toxic metals in the wastewater are effectively separated by chelating adsorption, thereby realizing the recovery and utilization of rare earth metals or toxic metals in the wastewater.

[0057] (3) The rare earth or toxic metal adsorbed by the cellulose-intercalated Ni-Fe-Al hydrotalcite of the present invention has high dispersibility, which plays a doping and modification role on the spinel formed after calcination, reduces its grain size, promotes the oxygen transfer of the oxygen carrier, and simultaneously generates abundant catalytic activation sites, thereby improving the medium and low temperature oxygen release of the oxygen carrier and the activation and conversion ability of the fuel, which is beneficial to the medium and low temperature conversion of the fuel.

[0058] (4) The present invention calcines the cellulose intercalated Ni-Fe-Al hydrotalcite composite with metal adsorbed between layers, so that the cellulose between the hydrotalcite layers is removed after calcination, thereby improving the porosity and specific surface area of ​​the oxygen carrier and increasing the contact area between the oxygen carrier and the reaction fuel. The oxygen carrier has good circulation capacity when reacting in a wide temperature range, can maintain high H2 and CO selectivity at a high conversion rate, and at the same time has good anti-sintering and anti-carbon deposition capabilities.

[0059] (5) The oxygen carrier preparation conditions of the present invention are simple and easy to control, the cost is low, and the effects of high stability and high reaction activity can be achieved, which is conducive to large-scale application in chemical chain steam reforming. Compared with the existing oxygen carrier preparation methods, the cellulose intercalation hydrotalcite method is combined with the adsorption and separation of rare earth metals / toxic metals, which improves the medium and low temperature oxygen release capacity and catalytic effect of the oxygen carrier while recycling the rare earth metals or toxic metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 The X-ray diffraction patterns of the cellulose intercalated Ni—Fe—Al type hydrotalcite obtained in Example 1 and the Ni—Fe—Al type hydrotalcite obtained in Comparative Example 3 are shown.

[0061] Figure 2 These are X-ray diffraction patterns of the metal-doped / cellulose-intercalated Ni—Fe—Al hydrotalcite-derived oxygen carrier obtained in Example 1 and the Ni—Fe—Al hydrotalcite-derived oxygen carrier obtained in Comparative Example 3.

[0062] Figure 3 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Example 1 on methane.

[0063] Figure 4 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Example 2 on methane.

[0064] Figure 5 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Example 3 on methane.

[0065] Figure 6This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Example 4 on methane.

[0066] Figure 7 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Comparative Example 1 on methane.

[0067] Figure 8 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Comparative Example 2 on methane.

[0068] Fig. 9 This is a diagram showing the reforming effect of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier obtained in Comparative Example 3 on methane.

[0069] Fig.10 This is a diagram showing the reforming effect of the oxygen carrier derived from the cellulose intercalated Ni-Fe-Al hydrotalcite obtained in Comparative Example 4 on methane. DETAILED DESCRIPTION

[0070] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0071] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0072] Example 1

[0073] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 6.28 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate nonahydrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0074] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 0.0075 mol of lanthanum nitrate hexahydrate and 0.0075 mol of yttrium nitrate hexahydrate were dissolved in 100 ml of water to prepare a rare earth metal mixed solution with a total metal ion concentration of 0.15 mol / L. 5 g of cellulose-intercalated hydrotalcite composite was added to the rare earth metal mixed solution at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water until The cellulose-doped Ni-Fe-Al hydrotalcite precursor was neutralized and then dried in an oven at 105°C for 2h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h in stages (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0075] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was as high as 98.98%, the hydrogen selectivity was as high as 100.00%, and the carbon monoxide selectivity was as high as 94.62%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O2 was injected into the quartz tube at a rate of 0.1 ml / min for 7 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 13.31 mol·h -1 kg -1 , with a purity of 80.26%.

[0076] Example 2

[0077] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 9.42 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0078] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 0.0075 mol of lanthanum nitrate hexahydrate and 0.0075 mol of yttrium nitrate hexahydrate were dissolved in 100 ml of water to prepare a rare earth metal mixed solution with a total metal ion concentration of 0.15 mol / L. 5 g of cellulose-intercalated hydrotalcite composite was added to the rare earth metal mixed solution at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water until The cellulose-doped Ni-Fe-Al hydrotalcite precursor was neutralized and then dried in an oven at 105°C for 2h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h in stages (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0079] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was as high as 97.35%, the hydrogen selectivity was as high as 99.26%, and the carbon monoxide selectivity was as high as 79.34%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O2 was injected into the quartz tube at a rate of 0.1 ml / min for 7 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 5.91 mol·h -1 kg -1 , with a purity of 70.44%.

[0080] Example 3

[0081] (1) Preparation of cellulose intercalated Ni-Fe-Al type hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 12.56 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated type hydrotalcite composite.

[0082] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 0.0075 mol of lanthanum nitrate hexahydrate and 0.0075 mol of yttrium nitrate hexahydrate were dissolved in 100 ml of water to prepare a rare earth metal mixed solution with a total metal ion concentration of 0.15 mol / L. 5 g of cellulose-intercalated hydrotalcite composite was added to the rare earth metal mixed solution at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water until The cellulose-doped Ni-Fe-Al hydrotalcite precursor was neutralized and then dried in an oven at 105°C for 2h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h in stages (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0083] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was as high as 98.30%, the hydrogen selectivity was 95.03%, and the carbon monoxide selectivity was 80.49%. After the steam reforming stage and the methane stage, nitrogen was introduced for 10 min at a rate of 90 ml / min. Then, H2O was injected into the quartz tube at a rate of 0.1 ml / min for 27 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 13.43 mol·h -1 kg -1 , with a purity of 82.34%.

[0084] Example 4

[0085] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 6.28 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate nonahydrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0086] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 5 g of cellulose-intercalated hydrotalcite complex was added to a metal wastewater solution (metal electroplating wastewater, rich in metal ions such as Cr, Cu, and Pb, wherein the Cr ion concentration was about 0.15 mol / L) at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water to neutrality, and then dried in an oven at 105°C for 2 h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorption of rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorption of rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2 h and 900°C for 4 h (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0087] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was as high as 100.00%, the hydrogen selectivity was as high as 98.38%, and the carbon monoxide selectivity was as high as 57.17%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O2 was injected into the quartz tube at a rate of 0.1 ml / min for 7 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 11.96 mol·h -1 kg -1 , with a purity of 74.84%.

[0088] Comparative Example 1

[0089] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 15.7 g cellulose powder (average particle size of 200 μm) was added to the mixed solution of urea and sodium hydroxide at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0090] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 0.0075 mol of lanthanum nitrate hexahydrate and 0.0075 mol of yttrium nitrate hexahydrate were dissolved in 100 ml of water to prepare a rare earth metal mixed solution with a total metal ion concentration of 0.15 mol / L. 5 g of cellulose-intercalated hydrotalcite composite was added to the rare earth metal mixed solution at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water until The cellulose-doped Ni-Fe-Al hydrotalcite precursor was neutralized and then dried in an oven at 105°C for 2h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h in stages (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0091] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was as high as 99.69%, the hydrogen selectivity was 90.32%, and the carbon monoxide selectivity was 72.48%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O was injected into the quartz tube at a flow rate of 0.1 ml / min for 27 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 15.70 mol·h -1 kg -1 , with a purity of 78.21%.

[0092] Comparative Example 2

[0093] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 3.14 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0094] (2) Preparation of metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carriers: 0.0075 mol of lanthanum nitrate hexahydrate and 0.0075 mol of yttrium nitrate hexahydrate were dissolved in 100 ml of water to prepare a rare earth metal mixed solution with a total metal ion concentration of 0.15 mol / L. 5 g of cellulose-intercalated hydrotalcite composite was added to the rare earth metal mixed solution at 300 r / min and stirred for 120 min. The precipitate was filtered and washed with deionized water until The cellulose-doped Ni-Fe-Al hydrotalcite precursor was neutralized and then dried in an oven at 105°C for 2h to obtain a cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals. The cellulose-intercalated Ni-Fe-Al hydrotalcite precursor after adsorbing rare earth metals was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h in stages (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier.

[0095] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was 99.45%, the hydrogen selectivity was 74.61%, and the carbon monoxide selectivity was 63.48%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O was injected into the quartz tube at a rate of 0.1 ml / min for 27 min under a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 1.48 mol·h -1 kg -1 , with a purity of 100%.

[0096] Comparative Example 3

[0097] (1) Dissolve 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate in 100 ml of deionized water to prepare a metal solution with a metal ion concentration of 1 mol / L; dissolve 0.132 mol sodium hydroxide and 0.066 mol anhydrous sodium carbonate in 200 ml of water to obtain a 1 mol / L mixed alkaline solution. The metal solution was quickly poured into the mixed alkaline solution at a speed of 500 r / min to obtain a precipitate. After aging at room temperature for 24 hours, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 hours to obtain a hydrotalcite precursor. The hydrotalcite precursor was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2h and 900°C for 4h (heating rate 10°C / min). After cooling, it was ground through an 80-mesh sieve to obtain an oxygen carrier derived from a Ni-Fe-Al hydrotalcite without cellulose intercalation.

[0098] (2) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was 53.68%, the hydrogen selectivity was 31.10%, and the carbon monoxide selectivity was 68.89%. The steam reforming stage was carried out after the methane stage by introducing nitrogen at a flow rate of 90 ml / min for 10 min. Then, H2O was injected into the quartz tube at a rate of 0.1 ml / min for 27 min under a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 8.88 mol·h -1 kg -1 , the purity is only 70.03%.

[0099] Comparative Example 4

[0100] (1) Preparation of cellulose intercalated Ni-Fe-Al hydrotalcite composite: 0.35 mol sodium hydroxide and 0.4 mol urea were dissolved in 200 ml water to obtain a 3.75 mol / L mixed solution, which was cooled to 12°C. 6.28 g cellulose powder (average particle size of 200 μm) was added to the urea and sodium hydroxide mixed solution at a speed of 700 r / min and stirred for 60 min to obtain a cellulose mixed alkaline solution. 0.05 mol nickel nitrate hexahydrate, 0.025 mol iron nitrate nonahydrate and 0.025 mol aluminum nitrate were dissolved in 100 ml deionized water to obtain a metal solution with a metal ion concentration of 1 mol / L; the metal solution was added dropwise to the cellulose composite alkaline solution at 500 r / min and stirred for 15 min to obtain a precipitate. After aging at room temperature for 24 h, the precipitate was filtered and rinsed with deionized water until neutral, and then dried in an oven at 70°C for 24 h to obtain a cellulose intercalated hydrotalcite composite.

[0101] (2) Preparation of cellulose intercalated Ni-Fe-Al type hydrotalcite-derived oxygen carrier: The cellulose intercalated Ni-Fe-Al type hydrotalcite precursor was placed in a muffle furnace and calcined in an air atmosphere at 500°C for 2 h and 900°C for 4 h in stages (heating rate 10°C / min). After cooling, the mixture was ground through an 80-mesh sieve to obtain the cellulose intercalated Ni-Fe-Al type hydrotalcite-derived oxygen carrier.

[0102] (3) Evaluation of oxygen carrier reaction characteristics: The reaction of methane chemical chain to synthesis gas was carried out in a small fixed bed. 1.45g of oxygen carrier was placed in the center of the quartz tube, and quartz wool was plugged at both ends to fix the oxygen carrier. Nitrogen was introduced for 10 minutes to exhaust the air. After the atmosphere furnace was heated to 750°C, the quartz tube was placed in the atmosphere furnace and the temperature was stabilized. Then the gas was switched to 100ml / min of methane (10% CH4 / 90% N2). The reaction time at this stage was 27 minutes. The synthesis gas obtained by the reaction was collected with an air bag and its composition was analyzed by gas chromatography. After analysis, the methane conversion rate was 94.93%, the hydrogen selectivity was 55.24%, and the carbon monoxide selectivity was 46.41%. After the steam reforming stage and the methane stage, nitrogen was introduced for 10 min at a rate of 90 ml / min. Then, H2O was injected into the quartz tube at a rate of 0.1 ml / min for 27 min at a nitrogen flow rate of 90 ml / min. The gas obtained by the reaction was collected with a gas bag and its composition was analyzed. The hydrogen yield was 13.78 mol·h -1 kg -1 , with a purity of 92.05%.

[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier, characterized in that: The following steps are involved: (1) adding cellulose to a mixed solution of urea and alkali salt to prepare a cellulose mixed alkali solution; (2) adding a mixed aqueous solution of nickel salt, aluminum salt and iron salt to a mixed alkaline solution of cellulose for coprecipitation, aging, filtering, washing and drying to obtain a cellulose intercalated hydrotalcite precursor; (3) adding the cellulose intercalated hydrotalcite precursor into a metal solution or metal wastewater for immersion adsorption, filtering, washing, and drying to obtain a cellulose intercalated Ni-Fe-Al hydrotalcite composite with interlayer adsorption of metal; (4) The cellulose intercalated Ni-Fe-Al type hydrotalcite composite with interlayer adsorbed metal is calcined at 400-900° C. for 4-8 hours to obtain a metal-doped / cellulose intercalated Ni-Fe-Al type hydrotalcite-derived oxygen carrier.

2. The method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier according to claim 1, characterized in that: The total molar ratio of the mass of the cellulose to the mass of the urea and the alkali salt in step (1) is 8.37-16.74 g:1 mol; The molar ratio of the mass of the cellulose in step (1) to the total metal of the nickel salt, the aluminum salt and the iron salt is 62.8 to 125.6 g: 1 mol; The molar ratio of the nickel salt, iron salt and aluminum salt in step (2) is 2-3:1:1; In step (3), the mass ratio of the cellulose intercalated Ni-Fe-Al hydrotalcite composite to the total molar ratio of metal cations in the metal solution or metal wastewater is 1 g: 5 to 25 mmol; In the metal solution and metal wastewater of step (3), the metal is at least one of La, Y, Ce, Zr and Cr; and the metal exists in the solution and wastewater in the form of soluble salt.

3. The method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier according to claim 1 or 2, characterized in that: The average particle size of the cellulose in step (1) is 50 to 200 μm; The coprecipitation time in step (2) is 10 to 25 minutes; The aging time in step (2) is 12 to 24 hours; The soaking and adsorption time in step (3) is 60 to 240 minutes and the temperature is 10 to 35° C. The calcination temperature in step (4) is 500-900° C. and the calcination time is 2-6 hours; The calcination in step (4) is carried out in an air atmosphere; The heating rate of the calcination in step (4) is 2 to 15°C / min.

4. The method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier according to claim 1 or 2, characterized in that: In the mixed solution of urea and alkali salt in step (1), the molar ratio of urea to alkali salt is 1-2:1; the alkali salt is at least one of sodium hydroxide and potassium hydroxide; In the mixed solution of urea and alkali salt in step (1), the total molar concentration of urea and alkali salt is 3.75-6 mol / L; In step (2), the nickel salt is nickel nitrate; the aluminum salt is aluminum nitrate; and the iron salt is iron nitrate; In the mixed aqueous solution of nickel salt, aluminum salt and iron salt in step (2), the total concentration of cations is 0.1 to 1 mol / L; The concentration of metal in the metal solution and metal wastewater in step (3) is 0.05-0.25 mol / L.

5. The method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier according to claim 1 or 2, characterized in that: In the mixed solution of urea and alkali salt in step (1), the molar ratio of urea to alkali salt is 1.14:1; The total molar ratio of the mass of the cellulose to the urea and the alkali salt in step (1) is 8.37 g: 1 mol; The molar ratio of the mass of the cellulose in step (1) to the total metal of the nickel salt, the aluminum salt and the iron salt is 62.8:1 mol; The molar ratio of the nickel salt, iron salt and aluminum salt in step (2) is 2:1:1; In the metal solution and metal wastewater of step (3), the metal is at least one of La, Y and Cr; The total molar ratio of the mass of the cellulose intercalated Ni-Fe-Al hydrotalcite composite to the total molar ratio of the metal cations in the metal solution or metal wastewater in step (3) is 1 g:3 mmol.

6. The method for preparing a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier according to claim 1, characterized in that: The coprecipitation in step (2) is carried out at a stirring speed of 500 to 800 r / min; The immersion adsorption in step (3) is carried out at a stirring speed of 200 to 500 r / min; After the cellulose intercalated Ni-Fe-Al type hydrotalcite composite with interlayer metal adsorption in step (4) is calcined, it needs to be ground and sieved.

7. An oxygen carrier derived from a metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-like substance obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier as claimed in claim 7 in chemical chaining water vapor to produce synthesis gas and pure hydrogen.

9. The use according to claim 8, characterized in that: Add the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier described in claim 7 into a fuel reactor, first introduce an inert gas to purge the air in the fuel reactor, then heat the fuel reactor to a reaction temperature, wait for the temperature of the fuel reactor to stabilize, introduce gas fuel, liquid fuel or solid fuel to produce synthesis gas, introduce an inert gas to purge the synthesis gas in the reactor after the reaction is completed, and introduce water vapor and an inert gas to the steam reactor after it is stabilized for steam reforming to produce hydrogen; The gas fuel is an alkane fuel diluted with inert gas to a volume percentage of 5-25%; the liquid fuel is alcohol or bio-oil fuel; and the solid fuel is biomass or organic waste solid fuel.

10. The use according to claim 9, characterized in that: The gas fuel is methane diluted with inert gas to a volume percentage of 5 to 25%; The flow rate of the gas fuel is 50-150 ml / min, and the introduction time is 20-180 min; The lattice oxygen molar ratio of the gas fuel, liquid fuel or solid fuel to the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite-derived oxygen carrier is 1.2 to 0.8:1; The molar ratio of water vapor to lattice oxygen in the oxygen carrier derived from the metal-doped / cellulose-intercalated Ni-Fe-Al hydrotalcite is 0.82 to 8.2:1; The reaction temperature is 500-900°C; The flow rate of the inert gas in the steam reforming stage is 50-100 ml / min; The steam injection rate during the steam reforming process is 0.1 to 10 ml / min, and the time is 20 to 180 min.

Citation Information

Patent Citations

  • Oxygen carrier and application thereof in chemical chain gasification of cellulose solid wastes

    CN115069256A

  • AlO2-intercalation hydrotalcite-like compound derived oxygen carrier as well as preparation and application thereof

    CN118543351A

  • Oxygen-carrier solid with sub-stoichiometric spinel for a chemical-looping redox process

    US20230415125A1